Temporal controls on silicic acid utilisation along the West Antarctic Peninsula - Swann, George E.A.; Pike, Jennifer; Leng, Melanie J.; Sloane, Hilary J.; Snelling, Andrea M. (Nature Publishing Group, 2017)
The impact of climatic change along the Antarctica Peninsula has been widely debated in light of atmospheric/oceanic warming and increases in glacial melt over the past half century. Particular concern exists over the impact of these changes on marine ecosystems, not only on primary producers but also on higher trophic levels. Here we present a record detailing the historical controls on the biogeochemical cycling of silicic acid [Si(OH)4] on the west Antarctica Peninsula margin, a region in which the modern phytoplankton environment is constrained by seasonal sea-ice. We demonstrate that Si(OH)4 cycling through the Holocene alternates between being primarily regulated by sea-ice or glacial discharge from the surrounding grounded ice-sheet. With further climate-driven change and melting forecast for the 21st Century, our findings document the potential for biogeochemical cycling and multi-trophic interactions along the peninsula to be increasingly regulated by glacial discharge, altering food-web interactions.